Liver Stiffness by ARFI does not Correlate with Decompensation and Portal Hypertension in Patients with Cirrhosis - Kidd Leong, Hoie; Gibson, Robert; Sood, Siddharth; Nadebaum, David; Gorelik, Alexandra; Nicoll, Amanda (Journal of Digestive Disorders And Diagnosis, 2017)
Background and Aims: Establishing the degree of fibrosis is important in determining the prognosis of patients with chronic liver disease. Acoustic Radiation Force Impulse Imaging (ARFI) has been validated as a reliable method to estimate liver fibrosis. It remains unclear if ARFI readings may be a useful way to stage patients with established cirrhosis and predict the development of complications. The aim of this study was to determine if ARFI liver stiffness measurements correlate with the severity of liver disease in patients with cirrhosis, and predict the development of complications and decompensation. Methods: All patients attending our institution who had a prior clinical diagnosis of cirrhosis and an ARFI liver stiffness measurement (LSM) over 26 months were included. Area under the receiver operating characteristic (AUROC) curves were calculated for ARFI detection of any complication, any varices, medium or large varices, moderate or severe ascites, encephalopathy, Child Pugh Grade B or C and MELD ≥15. Results: ARFI LSM did not correlate with complications: any complication (AUROC 0.672), any varices (0.631), medium or large varices (0.610), moderate or severe ascites (0.681), Child Pugh B/C (0.691) or MELD ≥15 (0.711). Hepatic encephalopathy did correlate with higher LSM (0.854), but only in a small number of cases. Conclusion: ARFI in patients with cirrhosis does not correlate with the presence of portal hypertension or decompensated liver disease.
Keywords: Elastography; Acoustic Radiation Force Impulse Imaging; ARFI; cirrhosis; varices; encephalopathy